Impact of ultrasonic mixing on virgin and waste vegetable oils for biodiesel production - Igbax, Saanyol Ityokumbul; Swartling, Daniel; ElSawy, Ahmed; Idem, Stephen (Frontiers in Energy Research, 2023)
This paper investigates the use of waste vegetable oil (WVO) for production of biodiesel. The study explores the improvement of biodiesel production using ultrasonic mixing to achieve high yields. Different oil streams, including virgin canola oil and WVO, were used as the raw material for the transesterification processes. These oils had different fatty acid contents as a result of environmental or previous processing conditions. The impact of free fatty acid (FFA) content on the resulting yield was assessed. It was demonstrated that the yield was influenced by production parameters such as reaction time, reaction temperature, molar/volume ratios of oil to alcohol, catalyst amount, and mechanical mixing. This was accomplished by automating the biodiesel production from WVO, thereby achieving improved processing and requiring minimal direct human involvement. A biodiesel production apparatus was developed with a Raspberry Pi 3 microcomputer to control the process. The particular choice of these process parameters depended on the particular oil type. This research used mixtures of virgin and waste vegetable oils at different volume ratios (oil to alcohol) of 4:1, 6:1, and 8:1, which was determined by the FFA content of the oil. In addition to mechanical mixing, ultrasonication rated at 500 W, 20 kHz was used to enhance mixing by adding 450 kJ to the process, thereby reducing both the processing time and the amount of methoxide needed to perform a base-catalyzed transesterification. This research demonstrated that optimal yield depends on temperature, catalyst concentration, FFA content of the oil, and the energy introduced by sonication.